A Randomized Controlled Trial Evaluating Virologic and Renal Outcomes After Switching from TDF+FTC or 3TC+EFV to TDF/3TC/DTG (TLD) Versus DTG+3TC in Virologically Suppressed Thai PWH – A Pilot Study - Kanogtorn, Sathaporn; Putcharoen, Opass; Patamatamkul, Samadhi (Current HIV Research, 2025)
<span class=
Keywords: switching regimen